Antibacterial Effect of Red Laser Therapy on Enterococcus faecalis Using Different Photosensitizers: An In Vitro Study - Franz Torres; Adrian Mallma; Americo Munayco; Oscar Sotomayor; Franco Mauricio; Frank Mayta-Tovalino (Hindawi Limited, 2022)
Objective. To assess the antibacterial effect of red laser using different photosensitizers such as methylene blue and malachite green on monoradicular premolars contaminated with E. faecalis ATCC 29212. Methods. This was an in vitro experimental study. Monoradicular premolars (44, 45, 34, and 35) were used, which were treated with ProTaper Next. After instrument change, irrigation, disinfection, and aspiration were performed with 2 ml of 4% NaOCl with a NaviTip 30°G needle (Ultradent, South Jordan, UT, USA). Group 1: RL + MB (red laser associated with methylene blue photosensitizer), group 2: RL + MG (red laser associated with malachite green photosensitizer), and group 3: control (no treatment). The E. faecalis strain was cultured on trypticase soy agar (TSB) (Difco, Detroit, MI, USA) and incubated at 37°C for 24 h. After the incubation period, colony-forming units (CFU/ml) of each group were counted using the plate count method. The ANOVA test was used with a significance level of p<0.05. Results. Group 1 had the lowest antibacterial contamination as it averaged only 530 ± 581.3 CFU/ml, while group 2 had the highest contamination with an average of 1990 ± 542.5 CFU/ml. Comparison revealed that there were statistically significant differences between the RL + MB and RL + MG groups (p<0.001). Conclusions. Group 1 had the best antimicrobial potential because it presented the lowest contamination in CFU/ml of E. faecalis compared to group 2 and group 3.